Prognostic Value of New‐Generation Troponins in ST‐Segment–Elevation Myocardial Infarction in the Modern Era: The RUTI‐STEMI Study. Issue 12 (23rd December 2017) - Cediel, Germán; Rueda, Ferran; García, Cosme; Oliveras, Teresa; Labata, Carlos; Serra, Jordi; Núñez, Julio; Bodí, Vicent; Ferrer, Marc; Lupón, Josep; Bayes‐Genis, Antoni
Abstract : Background: In ST‐segment–elevation myocardial infarction (STEMI), troponins are not needed for diagnosis: symptoms and ECG data are sufficient to activate percutaneous coronary intervention. This study explored the prognostic value of new‐generation troponins in a real‐life cohort contemporarily treated for STEMI. Methods and Results: We studied 1260 consecutive patients with primary STEMI treated with percutaneous coronary intervention between February 22, 2011, and August 31, 2015. We collected data on clinical characteristics and major adverse cardiovascular and cerebrovascular events (MACCEs) at 30 days and 1 year. Peak high‐sensitivity troponin T and sensitive‐contemporary troponin I levels were recorded. MACCEs occurred in 75 patients (6.1%) by day 30 and in 124 patients (10.8%) between day 31 and 1 year. A short‐term (0–30 days) multivariable Cox regression analysis revealed that age, Killip‐Kimball class, and left ventricular ejection fraction were independent predictors of MACCEs. In adjusted analysis, peak high‐sensitivity troponin T and sensitive‐contemporary troponin I were not significant (hazard ratio, 1.23 [95% confidence interval, 0.98–1.54] [ P =0.071]; and hazard ratio, 1.15 [95% confidence interval, 0.93–1.43] [ P =0.200], respectively). A long‐term (31 days–1 year) multivariable Cox regression analysis revealed that age, female sex, diabetes mellitus, prior coronary artery disease, Killip‐Kimball class, and left ventricular ejection fraction were statistically significantly associated with MACCEs. However, peak high‐sensitivity troponin T and peak sensitive‐contemporary troponin I were not significantly associated with MACCEs (hazard ratio, 1.03 [95% confidence interval, 0.88–1.20] [ P =0.715]; and hazard ratio, 0.99 [95% confidence interval, 0.85–1.15] [ P =0.856], respectively). Conclusions: In the modern era, new‐generation troponins do not provide significant prognostic information for predicting clinical events in STEMI. We should reconsider the value of serial troponin measurements for risk stratification in STEMI.